Effects of ownership structure on Malaysian companies performance - Noor Afza Amran; Ayoib Che Ahmad (FEP, 2013)
The aim of this paper is to examine effects of managerial and family ownership structure on the company performance. The sample consists of four hundred and twenty companies listed on Bursa Malaysia for the year from 2003 to 2007. The study shows that equity ownerships in Malaysia are concentrated on few owners mainly by the State government, families or large corporations. Results reveal that managerial ownership relates significantly to return on assets (ROA) and return on equity (ROE) while family ownership relates significantly to Tobin’s Q, ROA and ROE. Results suggest that an increase in the proportion of insider ownerships enhances the company performance due to re-alignment of internal and external interests and reduction in conflict of interests among shareholders. The results further indicate that the firm performance decreases when the managers’ share ownership increases. Managers with greater control and large shareholdings are more concerned with their own self-interests than the interests of the shareholders at large.